Sand Dune Reclamation in Iraq-Present Status and Future Prospects - Dougrameji, J; Kaul, R N (Annals of Arid Zone, 2016)
Shiftlng clay and sand have resulted an imbalance between the human and animal population on the one band and the plant, water and land resources on the other. Drought. over-exploitation of natural vegetation and improper cultural operation accelerate the soil drift. A pbyta-reclamation technique has been postulated for the sand dune reclamation.